Bentuk Penyajian dan Keberfungsian Distraktor dalam Soal UTS Kelas X di SMK Muhammadiyah 2 Surakarta - Lestari, Titik; , Laili Etika Rahmawati, S.Pd., M.Pd (2017)
Abstract This research aims to describ presentation of distractor and the function of distractor in mid semester exam of 10th grade in SMK Muhammadiyah 2 Surakarta. The research is a descriptive qualitative. The object of this study is a grain of mid semester examdetractorsof 10th grade in SMK Muhammadiyah 2 Surakarta. Data sources obtained from Indonesian issues Class X year 2016/2017 at SMK Muhammadiyah 2 Surakarta. The method of collecting data uses documentation's method and content analysis. The analysis of the data in this study uses qualitative descriptive technique. The research has two results in this study. The first is there are 12 numbers distractor presentation in the form of words, 10 numbers in the form of a phrase, clause 14 in the form of numbers, 11 numbers in the form of sentences, and 3 numbers in the form of functioning distractors. The second is there are already functioning well and there were not functioning properly. There are 148 or 74% distractor's data are not functioning properly and 52 or 26% data distractor's data are functioning properly. A hard question that could be done by the students there are 19 numbers or as much as 38%. Problem being that can be done by the students, there are 15 numbers or as much as 30%. An easy matter that can be done by the students, there are 16 numbers or as much as 32%.